Developing audio-based pop-up book learning media for introducing numbers 1-10 for children with intellectual disability grade ii in SLB negeri 1 barru - Ade Magfira A; Triyanto Pristiwaluyo; Syamsuddin Syamsuddin (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This research aimed to develop a product in the form of an audio-based pop-up book learning media for introducing numbers 1-10. The focus of this research is to find out the process of developing learning media starting from analyzing teacher needs, designing pop-up book learning media, validating media content, to determining the effectiveness of pop-up book learning media based on audio introduction to numbers 1-10. This research utilized the 4D development model (four-D model) modified into 3 stages without reducing the value or development itself. Data collection techniques in this study used interview techniques and questionnaires with descriptive qualitative and quantitative data analysis. The results of the study on the needs analysis indicated that teachers and students need learning media for the introduction of numbers 1-10. The design of the media is a 3D book that has a speaker and is equipped with a user manual. Content validity was tested using the Gregory formula with the results that have been declared valid for use, and the effectiveness of this media was analyzed using the Recude into different variables transformation using the SPSS program